2013
DOI: 10.1002/adma.201300550
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Dominance of Vertical Dislocations in High‐Misfit Ge/Si(001) Films and Their Elimination by Deep Substrate Patterning

Abstract: An innovative strategy in dislocation analysis, based on comparison between continuous and tessellated film, demonstrates that vertical dislocations, extending straight up to the surface, easily dominate in thick Ge layers on Si(001) substrates. The complete elimination of dislocations is achieved by growing self-aligned and self-limited Ge microcrystals with fully faceted growth fronts, as demonstrated by AFM extensive etch-pit counts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
58
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 24 publications
1
58
0
Order By: Relevance
“…To this end, is necessary to form the coalesced film from a set of Ge pillars featuring fully pyramidal top faceting, as found for narrow Si pillars and higher growth temperature shown in Figure 2. In refs [7], [9] and [10] we indeed demonstrated that no threading-dislocations are present in the upper part of the crystals, where the merging induced by annealing begins. Any additional dislocations nucleating during coalescence would therefore have to reside in a cylindrical expanding bridge, which is still surrounded by free surfaces.…”
Section: Phase-field Simulationsmentioning
confidence: 58%
“…To this end, is necessary to form the coalesced film from a set of Ge pillars featuring fully pyramidal top faceting, as found for narrow Si pillars and higher growth temperature shown in Figure 2. In refs [7], [9] and [10] we indeed demonstrated that no threading-dislocations are present in the upper part of the crystals, where the merging induced by annealing begins. Any additional dislocations nucleating during coalescence would therefore have to reside in a cylindrical expanding bridge, which is still surrounded by free surfaces.…”
Section: Phase-field Simulationsmentioning
confidence: 58%
“…Subsequent material deposition eventually yields a region of the crystal that is completely free from dislocations, although no annealing was performed. 16,18,19 Such an approach has been shown to…”
mentioning
confidence: 99%
“…As already widely reported in the literature, the epitaxial growth of wurtzite GaN on planar 6−11 and patterned 12,13 Si(1 1 1) substrates is favored by the 3-fold surface symmetry, compared to the 4-fold surface symmetry of Si(0 0 1). 14 Additionally, the use of deeply patterned substrates with faceted features at the micrometersize scale would be beneficial for reducing the density of dislocations, 15,16 as well as for improving the light extraction efficiency 17−19 and directionality 20,21 in GaN-based lightemitting diodes. These issues call for the analysis of GaN nucleation and growth on high-index Si surfaces, e.g., {1 1 3} and {15 3 23}, which is a challenging task not widely investigated so far.…”
Section: ■ Introductionmentioning
confidence: 99%